The Weathered Corrugations of His Face: A Performative Reflection on Nelson Mandela, Self, and the Call for Racial (Un)Becoming - Badenhorst, Paul (Forum, qualitative social research, 2015)
On the occasion of the first anniversary of the death of Nelson Rolihlahla MANDELA, this self-exploratory narrative study utilizes a Butlerian performative theoretical framework to both uncover discursively regulated social practices as generative of raced identity ensconced in belonging, and the undoing of such identity through the redeployment of social practices predicated instead on a Weltanschauung of becoming. While the accountable subject of autoethnographic work is concomitantly problematized, fluid subjectivity is itself demonstrated as crucial to historical accountability. A resultant appeal for white South Africans to actively begin the work of defamiliarizing themselves with the sanitized dominant popular culture representation of the peace icon, this research ultimately calls for new existential reflection upon the face of Nelson MANDELA so as to begin uncovering its deeper historical significance, contemporary relevance, and the future ethical imperative it demands of those who come from a liminal position of, as J.M. COETZEE once wrote, "no longer European, not yet African" (1988, p.11). In short, it is argued that white South Africans need to move from a condition of belonging predicated on raced identity to one of transracial—and even interracial—African becoming.URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs150223